PENGARUH PERHATIAN ORANG TUA TERHADAP KEDISIPLINAN BELAJAR SISWA - Sudarto Sudarto; Muliadi Muliadi; Ryan Ryan (JOEL: Journal of Educational and Language Research, 2022)
This research was a correlation study that aimed to determine whether there was or there was not an influence from the parental attention to the learning discipline of fifth grade students at SD Inpres 5/81 Tibojong. Research data obtained through a questionnaire. The population in the study were all fifth grade students of SD Inpres 5/81 Tibojong for the academic year 2021/2022 in totaling 69 people. The sample in the study amounted to 69 people (saturated sample). Data analysis techniques include Simple Linear Regression Analysis and Significance Test. The results showed that the value of tcount (2.474) > ttable (1.675). Conclusion: the parental attention had a significant effect to the learning discipline of fifth grade students at SD Inpres 5/81 Tibojong.